Optimalisasi Pencegahan Penularan Covid 19 Melalui Peningkatan Peran Unit Kesehatan Sekolah (UKS) - Yusran Hasymi; Rina Delfina; Maiyulis Maiyulis (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Coronavirus Disease 2019 (Covid 19) is rapidly spreading throughout the world, including Indonesia. Positive confirmed cases rose significantly in the period May-August 2021. Cases in Bengkulu City showed as many as 4,173 people, 3,905 people recovered, 100 people died, and 663 suspected cases. The government has made restrictions on community activities, including learning in schools. Some schools continue to carry out face-to-face learning by implementing strict health protocols. The spread of Covid 19 can be prevented by increasing public knowledge, including teachers and students by providing information about preventing transmission. The School Health Unit (UKS) as a driving force in schools can provide correct information to teachers and students. UKS is a health program implemented by schools to provide health education, health services and foster a healthy school environment. The purpose of this activity is to increase the knowledge and attitudes of teachers and students towards efforts to prevent and transmit Covid 19 in schools, families, and communities. The method of this activity is communication, information, and observation to teachers and students at SMPIT Al-Hasanah Bengkulu City. This activity can measure the level of knowledge and attitudes of teachers and students before and after the activity to produce increased knowledge of the prevention and transmission of Covid 19 in schools and the community. Students become the most important part to overcome the spread in schools through increasing the role of UKS.